Active cooling based battery thermal management using composite phase change materials. (February 2019) - Zhao, Yanqi; Zou, Boyang; Li, Chuan; Ding, Yulong
Abstract: Thermal management system is essential for lithium-ion batteries in electric vehicle to control operating temperature and temperature differences. Phase change material (PCM) is commonly used in the study of battery thermal management system (BTMS). However, with low thermal conductivity, pure PCM is not sufficient for transferring the heat generated from battery cells. To resolve this problem, the thermal conductivity of PCM was enhanced using cooper foam. Active liquid cooling was also combined with copper foam/paraffin composite phase change material (CPCM) to provide extra cooling ability. The cooling tube is evenly distributed in the copper foam, and a coolant is circulated through the tube. The copper foam has a porosity of 98% and pore size of 20 ppi, and the paraffin has a melting point of 25 °C. A three-dimensional numerical model for the BTMS based on PCM and active liquid cooling was performed using ANYSYS FLUENT. The impact of the velocity of liquid inlet and material module on the BTMS was examined regarding the evolution of thermal management performance. A significant improvement of thermal management using CPCM and liquid cooling was observed with 14 °C of lower cell temperature.